Mathematische Modelle und Naturerkenntnis (mathematica didactica, 2004)
In question are the peculiarities of an understanding of nature being founded on mathematical models, its range and its boundaries as well. Mathematics is not external to the process of cognition, but is playing an active role. In opposition to the empiristic conception of the scientific mainstream, the results of „objective knowledge“ are affected by the specific method creating them.